2022
DOI: 10.33542/sds2022-0122-3
|View full text |Cite
|
Sign up to set email alerts
|

Sociálna spravodlivosť a starobné dôchodkové sporenie v SR

Abstract: Sociálna spravodlivosť ako kľúčová hodnota sociálnej politiky predstavuje neoddeliteľnú súčasť systému sociálneho zabezpečenia každého demokratického a právneho štátu Západnej civilizácie. Vedecká monografia sa zameriava na sociálnu spravodlivosť v starobnom dôchodkovom systéme Slovenskej republiky v časovom diapazóne 2004 - 2022. Pozornosť je dominantne zameraná na II., tzv. kapitalizačný dôchodkový pilier. Ciele vedeckej monografie korešpondujú s vybranými cieľmi formulovanými v rámci riešenia vedeckého proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…In relation to the valorization (indexation?) in previous calendar years and electoral periods (see Geffert -Rovenská, 2022a, b for more details), it can be concluded that it is confirmed that centre-right and right government coalitions prefer valorizations based on percentage rather than across-the-board increases in pension benefits. Such value preferences, and indeed understandings of social justice in the welfare state system, are based on Titmus's corporatist, and therefore power-type, understanding of social policy and welfare.…”
Section: Conclusion and Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In relation to the valorization (indexation?) in previous calendar years and electoral periods (see Geffert -Rovenská, 2022a, b for more details), it can be concluded that it is confirmed that centre-right and right government coalitions prefer valorizations based on percentage rather than across-the-board increases in pension benefits. Such value preferences, and indeed understandings of social justice in the welfare state system, are based on Titmus's corporatist, and therefore power-type, understanding of social policy and welfare.…”
Section: Conclusion and Discussionmentioning
confidence: 68%
“…At this point, it is necessary to note that ideology in this paper is understood objectively in philosophical-political terms (not negatively populist-political) in a neutral fashion as a set of values, not in a Marxist negative sense. (For more details see Šaradín, 2001;Bauer, 1991;Geffert, 2014;Geffert, 2021a,b). Despite the facts above, as Table 1 shows, from an axiological and ideological point of view, the governments of 2020 to 2023 (the 2020-2024 government period) can be characterized as relatively stable and consistent in terms of values.…”
Section: Slovak Republic Political Situation In Diapason 2020 -2023mentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, it is necessary to note that ideology in this paper is understood objectively in philosophical-political terms (not negatively populist-political) in a neutral fashion as a set of values, not in a Marxist negative sense. (For more details see Šaradín, 2001;Bauer, 1991;Geffert, 2014;Geffert, 2021a,b). in consumer prices for elderly households determined by the Statistical Office of the Slovak Republic (according to pensioners' purchasing behavior), usually calculated for the first half of the calendar year 2021.…”
Section: Slovak Republic Political Situation In Diapason 2020 -2023mentioning
confidence: 99%
“…It is polyparadigmatically viewed from many perspectives-political, economic, legal, sociological, and psychological (Geffert, 2021a,b;Geffert -Rovenská, 2022a;Geffert -Rovenská 2022b, Baláž, 2012Košta, 2017;Bačová -Kostovičová, 2018;. The unifying solution of individual social situations in the lives of (among others) the elderly is their standard of living.…”
Section: Introductionmentioning
confidence: 99%